QUALITY OF CARE STARTS WITH CAREGIVERS –EXPLORING EMOTIONAL INTELLIGENCE IN GERIATRIC SETTINGS - Nagara, Nesreen (E-Journal VFU, 2025)
This study explores the relationship between emotional intelligence, work commitment, and quality of life among caregivers in geriatric institutions. It investigates whether emotional intelligence and commitment impact caregivers’ well-being and the quality of care they provide. The research highlights the unique emotional challenges these caregivers face and proposes an educational intervention model to enhance emotional intelligence and foster psychological resilience. By addressing caregivers’ emotional and psychological needs, the study aims to improve both their well-being and the quality of care for elderly residents in geriatric settings.